PENGARUH PENGEMBANGAN DAN MOTIVASI SERTA ETIKA KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PEGADAIAN SYARIAH SAMARINDA - Saripudin Saripudin (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
This study aims to determine whether there is influence significantly the development of employee productivity in the Islamic pawnshop Branch samarinda, to determine whether there are significant effect of work motivation islami on employee productivity in the Islamic pawnshop Branch samarinda and to find out if there is a significant influence work ethic of employee productivity in the Islamic pawnshop samarinda Branch. Results with the partial test shows that the variable Employee Development (X1) no significant effect on Employee Productivity in Islamic pawnshop Samarinda, variable work motivation Islami (X2) significantly affects the Employee Productivity in Islamic pawnshop Samarinda and variable work ethic of Islam (X3 ) significantly affects the Employee Productivity in Samarinda Islamic pawnshop.Keywords:  Employee development, employee motivation Islamic, Islamic work ethic and productivity of employees